PENERAPAN PEMBELAJARAN MODELQUANTUM TEACHINGDENGAN PENDEKATANPETAKONSEP SERTA PENGARUHNYA TERHADAPPEMAHAMAN KONSEP REAKSI REDOKS - Debora Bani; Khaeruman Khaeruman; Ratna Azizah Mashami (P-2623-0291)
Matter of Redox Reaction has conceptual and symbolic characteristic, therefore student was claimed to understanding the concept. Quantum teaching model of learning using concept map approach could give compatible condition for student to actively involved into learning process through experiencing and reaching their own knowledge so that positively impact to student conceptual understanding. The aim of this research was to developing knowledge and thinking skill to understanding chemistry concept. In form of quasi experimental, posttest only control group design was carried out. Sample consist of two class was selected by saturated sampling, experimental class was learned by quantum teaching model of learning using concept map approach and control class was learned by conventional method and concept map approach. Data collected by reasoning objective test for student conceptual understanding measurement. The data was analyzed by t-test for hypothesis test. Based on conceptual understanding data analysis on significance level 5%, it was obtained thitung<ttabel  (0,558 < 1,995). This research showed that quantum teaching model of learning using concept map approach was not influence student conceptual understanding in reqox reaction matter of learning.